2023
DOI: 10.3390/rs15081964
|View full text |Cite
|
Sign up to set email alerts
|

Application of YOLOv5 for Point Label Based Object Detection of Black Pine Trees with Vitality Losses in UAV Data

Abstract: Monitoring tree diseases in forests is crucial for managing pathogens, particularly as climate change and globalization lead to the emergence and spread of tree diseases. Object detection algorithms for monitoring tree diseases through remote sensing rely on bounding boxes to represent trees. However, this approach may not be the most efficient. Our study proposed a solution to this challenge by applying object detection to unmanned aerial vehicle (UAV)-based imagery, using point labels that were converted int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The model was trained using a 0.001 learning rate. We evaluate Mask-RCNN 27 , 28 , Faster-RCNN 29 , 30 , YOLO V3 31 , 32 , and YOLO V5 33 , 34 in comparison to our suggested system.…”
Section: Resultsmentioning
confidence: 99%
“…The model was trained using a 0.001 learning rate. We evaluate Mask-RCNN 27 , 28 , Faster-RCNN 29 , 30 , YOLO V3 31 , 32 , and YOLO V5 33 , 34 in comparison to our suggested system.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Hofinger P. et al used the YOLOv5 algorithm to monitor tree diseases where images were captured by a UAV. Results obtained from this study revealed that the architecture imposed by the YOLOv5 algorithm is suitable for the proposed task, thus enabling the detection of damaged black pines with a 95% confidence interval [ 14 ]. Lastly, the work carried out by Niu K. et al demonstrated that the use of YOLOv5 proves advantageous for fire detection.…”
Section: Related Workmentioning
confidence: 99%
“…As for the network architecture under YOLOv5, Desta Sandya Prasvita et al [13] compared the YOLOv5 network models, including YOLOv5s, YOLOv5m, YOLOv5l, and YOLOv5x, and pointed out that as the model size increases, training accuracy increases, but so does training time. Hofinger et al [14] compared various network architectures of YOLOv5 and ultimately chose to use YOLOv5s as their research architecture. Subsequent experiments demonstrated that this network architecture could achieve superior results with less workload.…”
Section: Introductionmentioning
confidence: 99%